2017
DOI: 10.1016/j.bbadis.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The Zn 2+ -sensing receptor, ZnR/GPR39, upregulates colonocytic Cl − absorption, via basolateral KCC1, and reduces fluid loss

Abstract: Administration of zinc, as a complement to oral rehydration solutions, effectively diminishes duration and severity of diarrhea, but it is not known whether it merely fulfills a nutritional deficiency, or if zinc has a direct role of regulating solute absorption. We show that Zn2+ acts via a specific receptor, ZnR/GPR39, to reduce fluid loss. Intestinal fluid secretion triggered by cholera toxin (CTx) was lower in WT mice compared to ZnR/GPR39 KO. In the absence of dietary Zn2+ we observed similar fluid accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 88 publications
0
41
0
Order By: Relevance
“…As the Malpighian tubules are typically involved in excretion (Chi et al, 2015;Halberg et al, 2015;Yin et al, 2017), one intriguing possibility is that zinc storage granules provide a source of zinc for the intestinal lumen. In this view, the Malpighian tubule principal cells would have a similar physiological purpose as the intestinal paneth cells in mammals, where the secreted zinc has been implicated in the maintenance of the stem cell niche and epithelial integrity (Geiser et al, 2012;Ohashi et al, 2016;Podany et al, 2016;Sunuwar et al, 2016Sunuwar et al, , 2017aSunuwar et al, , 2017b. Another possibility is that luminal zinc may function as a regulator for intestinal microbiota and endosymbionts, or for the control of a commonly occurring natural pathogen (Brownlie et al, 2009;Bonfini et al, 2016;Mistry et al, 2016;Martino et al, 2017;Martinson et al, 2017;Clark and Walker, 2018).…”
Section: Normal Dietmentioning
confidence: 99%
“…As the Malpighian tubules are typically involved in excretion (Chi et al, 2015;Halberg et al, 2015;Yin et al, 2017), one intriguing possibility is that zinc storage granules provide a source of zinc for the intestinal lumen. In this view, the Malpighian tubule principal cells would have a similar physiological purpose as the intestinal paneth cells in mammals, where the secreted zinc has been implicated in the maintenance of the stem cell niche and epithelial integrity (Geiser et al, 2012;Ohashi et al, 2016;Podany et al, 2016;Sunuwar et al, 2016Sunuwar et al, , 2017aSunuwar et al, , 2017b. Another possibility is that luminal zinc may function as a regulator for intestinal microbiota and endosymbionts, or for the control of a commonly occurring natural pathogen (Brownlie et al, 2009;Bonfini et al, 2016;Mistry et al, 2016;Martino et al, 2017;Martinson et al, 2017;Clark and Walker, 2018).…”
Section: Normal Dietmentioning
confidence: 99%
“…ZnR/Gpr39 was shown to play a regulatory role in sugar metabolism, neuronal transmission, and regulation of gut epithelia proliferation and absorption (30). Importantly, several studies showed that ZnR/Gpr39 ablation may result in perturbations of pancreatic endocrine functions, obesity, and gut permeability (47)(48)(49)(50)(51), and zinc itself or its transporters have also been associated with pancreatic function. Both proper glucose metabolism and an intact gut epithelial barrier are important for maintaining healthy bone homeostasis, especially under conditions of bone challenge, such as in the case of postmenopausal osteoporosis (52)(53)(54)(55)(56).…”
Section: Altered Bone Anabolic Functions In Znr/gpr39 2/2 Micementioning
confidence: 99%
“…Physiological relevance was further established when Zn 2+ release from Caco-2 colonocytes was sufficient to induce ZnR/GPR39-dependent cell growth and tight junction formation [69,89]. In addition, in a cholera toxin model of diarrhea or a dextran sodium sulfate model of colitis, ZnR/GPR39-dependent pathways were not activated following dietary Zn 2+ depletion [90,91]. Similarly, in the prostate, where there are high concentrations of Zn 2+ /citrate complex and transient release of this ion is likely to occur following cell death or changes in pH, ZnR/GPR39 is adapted to the relevant concentrations, which range from 10 to 200 µM [59].…”
Section: Znr/gpr39-dependent Signalingmentioning
confidence: 99%